2018
DOI: 10.1016/j.lwt.2017.10.023
|View full text |Cite
|
Sign up to set email alerts
|

The effect of semolina replacement with protein powder from fish (Pseudophycis bachus) on the physicochemical characteristics of pasta

Abstract: The effect of semolina replacement with protein powder from fish (Pseudophycis bachus) on the physicochemical characteristics of pasta

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
96
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(111 citation statements)
references
References 39 publications
12
96
1
2
Order By: Relevance
“…Furthermore, starch granules were less swollen in these samples, suggesting less starch gelatinization. The findings are in agreement with other reports that the addition of protein decreased the WHC of snacks …”
Section: Resultssupporting
confidence: 93%
“…Furthermore, starch granules were less swollen in these samples, suggesting less starch gelatinization. The findings are in agreement with other reports that the addition of protein decreased the WHC of snacks …”
Section: Resultssupporting
confidence: 93%
“…Pasta is durum wheat-based inexpensive food product, famous worldwide because of its low cost, versatility, convenience, and excellent shelf life attributes (Desai, Brennan, & Brennan, 2018;Littardi et al, 2019). Although durum wheat semolina is essential for providing the desirable textural and color characteristics during the cooking process (Yadav, Balasubramanian, Kaur, Anand, & Singh, 2012), more recently other grains have been used to partially replace it, offering an improved physical and nutritional qualities (Lu et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Most of these additional ingredients has focused on manipulation of glycaemic index (GI) since clinical reports have suggested that food with low GI has been directly associated with the reduced risks of hyperlipidaemia, cardiovascular diseases, extending satiety, and improved insulin sensitivity (Chillo, Ranawana, & Henry, 2011;Dona, Pages, Gilbert, & Kuchel, 2010). Researchers have developed the pasta with various bioactive ingredients such as pasta from fish material (Desai, Brennan, & Brennan, 2019;Desai et al, 2018;Parvathy, Bindu, & Joshy, 2017), mushroom powder-based pasta (Gao, Brennan, Mason, & Brennan, 2016;Lu et al, 2018), millets pasta (Gull, Prasad, & Kumar, 2015;Jalgaonkar & Jha, 2016;Kamble et al, 2019), cereal, pseudocereal, and super grain-enriched pasta (Benhur et al, 2015;Menga et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The development of texture parameters is a critical factor in ensuring consumer acceptance of products . The texture properties of pasta are mainly affected by its starch matrix network, gluten content, protein additions, and other ingredients.…”
Section: Resultsmentioning
confidence: 99%
“…The development of texture parameters is a critical factor in ensuring consumer acceptance of products. 45 The texture properties of pasta are mainly affected by its starch matrix network, gluten content, protein additions, and other ingredients. 44 Firmness is an interesting parameter, as it is associated with the force required to compress the pasta between the teeth.…”
Section: Chemical and Technical Characterization Of Fresh Pastamentioning
confidence: 99%